Respuestas

  • Usuario de Brainly
2014-01-15T02:23:51+01:00
Solución:
=> (sen(x)) / ( sen(x) + cos(x)) =  ( sec(x)) / ( sec(x) + csc(x))

=> .......................................   ( 1 / cos(x)) / ( 1/cos(x) + 1 / sen(x))
=>.......................................... ( 1 / cos(x)) / ( sen(x) + Cos(x) / (sen(x)*cos(x))
=>........................................... (cos(x)*sen(x)) / ( cos(x) {(sen(x) + cos(x)})
=>............................................ ( sen(x) / { sen(x) + cos(x)} => Que era lo que se quería demostrar.
suerte. Gnesiszarabia